Emerging Paradigms in the Prevention of Surgical Site Infection: The Patient Microbiome and Antimicrobial Resistance. (6th June 2022) - Long, Dustin R.; Alverdy, John C.; Vavilala, Monica S.
Abstract : This article summarizes new scientific evidence on the pathogenesis of surgical site infection, including the roles of the patient microbiome and antimicrobial resistance, and reviews changes in guidelines and clinical practices for prevention.